Evaluation of microbiological criteria, planktonic communities and trophic state of groundwater resources in Siwa Oasis, Western Desert, Egypt - Mohamad S. Abdelkarim; Mohamed H. H. Ali; Amal A. Othman; Khadiga M. Gaber; Abeer M. A. Mahmoud; Dalia M. Belal (Scientific Reports)
Abstract Due to their small size and the extreme environmental conditions in hyper-arid regions, wells are highly susceptible to disturbances. Western Desert wells are scarcely studied concerning their ecological status and the environmental factors affecting their aquatic communities. This study aimed to assess groundwater trophic states based on the microbial, phytoplankton and zooplankton composition in three drains and seventeen wells. Principal component analysis, based on physical and chemical parameters, classified the drains and wells into three groups differentiated as; (1) highly mineralized and eutrophic sites with an average conductivity of 12.01 mS/cm. (2) minimally mineralized and eutrophic sites with mean conductivity of 2.14 mS/cm, and (3) an intermediate group with mean conductivity of 7.77 mS/cm. The microbial load exceeded the recommended limits. Fecal coliforms, fecal streptococci and nitrogen-fixing bacteria revealing bacterial contamination in these wells. The studied drains and wells poorly characterized by planktonic species richness. The phytoplankton and zooplankton indices suggested that the ecological status was generally good, with mesotrophic levels. Both phytoplankton and zooplankton communities indicated a minimal disturbance in the drains and wells of Siwa Oasis, while the microbial characterization revealed that these ecosystems are vulnerable and affected by the human activities. This multidisciplinary approach of our study provides new ecological insights into groundwater systems in arid regions like Siwa Oasis. Our work offers baseline ecological data, identifies early warning indicators of water quality degradation, and contributes to a deeper understanding of the interaction between biological communities and groundwater quality.